Overcoming species barriers: an outbreak of Lagovirus europaeus GI.2/RHDV2 in an isolated population of mountain hares (Lepus timidus) - Aleksija S. Neimanis; Harri Ahola; Ulrika Larsson Pettersson; Ana M. Lopes; Joana Abrantes; Siamak Zohari; Pedro J. Esteves; Dolores Gavier-Widén (BMC Veterinary Research, 2018)
Abstract Background Prior to 2010, the lagoviruses that cause rabbit hemorrhagic disease (RHD) in European rabbits (Oryctolagus cuniculus) and European brown hare syndrome (EBHS) in hares (Lepus spp.) were generally genus-specific. However, in 2010, rabbit hemorrhagic disease virus 2 (RHDV2), also known as Lagovirus europaeus GI.2, emerged and had the distinguishing ability to cause disease in both rabbits and certain hare species. The mountain hare (Lepus timidus) is native to Sweden and is susceptible to European brown hare syndrome virus (EBHSV), also called Lagovirus europaeus GII.1. While most mountain hare populations are found on the mainland, isolated populations also exist on islands. Here we investigate a mortality event in mountain hares on the small island of Hallands Väderö where other leporid species, including rabbits, are absent. Results Post-mortem and microscopic examination of three mountain hare carcasses collected from early November 2016 to mid-March 2017 revealed acute hepatic necrosis consistent with pathogenic lagovirus infection. Using immunohistochemistry, lagoviral capsid antigen was visualized within lesions, both in hepatocytes and macrophages. Genotyping and immunotyping of the virus independently confirmed infection with L. europaeus GI.2, not GII.1. Phylogenetic analyses of the vp60 gene grouped mountain hare strains together with a rabbit strain from an outbreak of GI.2 in July 2016, collected approximately 50 km away on the mainland. Conclusions This is the first documented infection of GI.2 in mountain hares and further expands the host range of GI.2. Lesions and tissue distribution mimic those of GII.1 in mountain hares. The virus was most likely initially introduced from a concurrent, large-scale GI.2 outbreak in rabbits on the adjacent mainland, providing another example of how readily this virus can spread. The mortality event in mountain hares lasted for at least 4.5 months in the absence of rabbits, which would have required virus circulation among mountain hares, ...